Interface tailoring through covalent hydroxyl-epoxy bonds improves hygromechanical stability in nanocellulose materials. (6th October 2016) - Ansari, Farhan; Lindh, Erik L.; Furo, Istvan; Johansson, Mats K.G.; Berglund, Lars A.
Abstract: Wide-spread use of cellulose nanofibril (CNF) biocomposites and nanomaterials is limited by CNF moisture sensitivity due to surface hydration. We report on a versatile and scalable interface tailoring route for CNF to address this, based on technically important epoxide chemistry. Bulk impregnation of epoxide-amine containing liquids is used to show that CNF hydroxyls can react with epoxides at high rates and high degree of conversion to form covalent bonds. Reactions take place inside nanostructured CNF networks under benign conditions, and are verified by solid state NMR. Epoxide modified CNF nanopaper shows significantly improved mechanical properties under moist and wet conditions. High resolution microscopy is used in fractography studies to relate the property differences to structural change. The cellulose-epoxide interface tailoring concept is versatile in that the functionality of molecules with epoxide end-groups can be varied over a wide range. Furthermore, epoxide reactions with nanocellulose can be readily implemented for processing of moisture-stable, tailored interface biocomposites in the form of coatings, adhesives and molded composites.